Exploring the knowledge filter: how entrepreneurship and university-industry relations drive economic growth - Pamela Mueller (Technische Universität Bergakademie Freiberg, Fakultät für Wirtschaftswissenschaften, 2005)
Knowledge is recognized as a crucial element of economic growth in addition to physical capital and labor. Knowledge can be transformed into products and processes and is, in this way, exploited commercially. The ability to produce, identify, and exploit knowledge depends on the existing knowledge stock and the absorptive capacity of actors such as employees at firms and researchers at universities and research institutions. The existing knowledge stock might not be commercialized to its full extent; therefore, knowledge flows must occur and transmission channels are needed. The paper tests the hypotheses that entrepreneurship and university-industry relations are vehicles for knowledge flows and, thus, spur economic growth.
Keywords: M13; O18; O31; 330; Regional growth; regional development; Knowledge; Entrepreneurship; university-industry relations; Regionales Wachstum; Wissen; Unternehmer; Forschungskooperation; Theorie; Alte Bundesländer